2019
DOI: 10.1002/jmv.25594
|View full text |Cite
|
Sign up to set email alerts
|

Circulating miRNA expression profile and bioinformatics analysis in patients with occult hepatitis B virus infection

Abstract: Emerging suggest that microRNAs (miRNAs) play vital roles in the occurrence and development of hepatitis B virus (HBV) infectious disease. However, miRNAs in occult hepatitis B virus infection (OBI), a special stage of HBV infection, remain largely unknown. Herein, we conducted this study to identify differentially expressed miRNAs and then to investigate the potential roles of these miRNAs in OBI. Plasma miRNA expression profiles of three OBI patients and three healthy controls were analyzed with high through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…In a more recent study, miRNAs, including hsa-miR-25-3p, -486-5p, -92a-3p, and -1-3p, showed the ability to distinguish OBI from healthy controls efficiently, with an area under the curve value of 0.874, 0.776, 0.886, and 0.807, respectively. In total, 32 differentially expressed miRNAs were identified between OBI and the healthy controls by miRNA sequencing[ 86 ]. Compared with the case of the healthy controls, plasma miR-451a and miR-340-3p were significantly upregulated in OBI, making the authors propose these markers for distinguishing OBI from healthy donors[ 86 ].…”
Section: Mechanisms That Lead To Obimentioning
confidence: 99%
See 1 more Smart Citation
“…In a more recent study, miRNAs, including hsa-miR-25-3p, -486-5p, -92a-3p, and -1-3p, showed the ability to distinguish OBI from healthy controls efficiently, with an area under the curve value of 0.874, 0.776, 0.886, and 0.807, respectively. In total, 32 differentially expressed miRNAs were identified between OBI and the healthy controls by miRNA sequencing[ 86 ]. Compared with the case of the healthy controls, plasma miR-451a and miR-340-3p were significantly upregulated in OBI, making the authors propose these markers for distinguishing OBI from healthy donors[ 86 ].…”
Section: Mechanisms That Lead To Obimentioning
confidence: 99%
“…In total, 32 differentially expressed miRNAs were identified between OBI and the healthy controls by miRNA sequencing[ 86 ]. Compared with the case of the healthy controls, plasma miR-451a and miR-340-3p were significantly upregulated in OBI, making the authors propose these markers for distinguishing OBI from healthy donors[ 86 ].…”
Section: Mechanisms That Lead To Obimentioning
confidence: 99%
“…[7][8][9][10][11][12] Moreover, there is evidence that microRNAs (miRNAs) are differentially expressed in patients with OBI compared to healthy controls. 13 I MD, MSc. Physician, Department of Internal Medicine, Faculty of Medicine, Hospital das Clínicas, Universidade Federal de Minas Gerais (UFMG), Belo Horizonte (MG), Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, several lncRNA profiles of different stages of chronic HBV infection have been reported [ 15 19 ], and functional and mechanism studies further reveal that abnormally expressed lncRNAs might play important roles in the development of HBV infection, such as HULC [ 19 , 20 ], PCNAP1 [ 21 ], HOTTIP [ 22 ], lncRNA#32 [ 23 ], HOTAIR [ 24 ] and HEIH [ 19 ]. However, to our knowledge, unlike miRNAs [ 25 27 ], the lncRNA expression in OBI has been not yet investigated.…”
Section: Introductionmentioning
confidence: 99%